The organization of journalists in the Kurdistan Regional Government with professional ethics in social networking sites: Facebook for example - مراد, أ. د. هيرش رسول; يونس, هيفي عبد اللطيف (Sulaimani Journal for Humanities, 2025)
The issue of Ethics and Media professionals’ commitment to its principles is controversial and significant in itself. Putting into perspective today’s notable technological and scientific advancement, it became the subject of serious discussions and deliberations in the academic realms; platforms, tools and social media, through their characteristics and multi-services, offered another perspective to this issue. Facebook, as a notable example of these media and important factor of communication, according to the statistics in Iraq is one of the most used platforms, which the old-fashioned media intensely resort to it and engage their media professionals in it to spread their messages extensively and cover the events at broad level.So, the research aims at: identifying the level of media professionals’ commitment to the principles of their professions’ ethics at covering and disseminating information on their channels’ formal page in Facebook. This research, in terms of type, is in the category of descriptive researches, and used survey method to answer the questions and achieve its goals. As a research group, it comprises of all Kurdish media professionals, who live in Kurdistan Region, work in the formal established media institutions, admins and managers of Facebook in social media. Furthermore, as the channel media professionals, they publish their information and coverages there. Also, they amount to 230 media professionals of different (ethnicities, ages, professions, types of channels, types of channel ownership and political allegiance). The research came up with some conclusions such as: according to the results, the media professionals are committed to the veracity principle at a high level. Also, they are committed to the principles of objectivity, purity, privacy rights and impartiality at a lower level. Meanwhile, based on the researchers’ observations and follow-up on the posts and subjects, the opposite of this is seen. Though they might be few, the media professionals disseminated those subjects that badly affected the receivers. The characteristics of wholeness, number and imagery reality of the social media led the media professionals to spread their subjects more carefully and raise the level of their commitment to professional ethics principles, but the characteristic of velocity at the time of dissemination, many times, led the media professionals astray
Keywords: Level; Commitment; Journalist; Professional Ethics; Kurdistan Region; Social Networks; Facebook